Who wants women to run? an investigation of gender differences in patterns of support among Irish local election candidates - Mc Elroy, Gail; Keenan, Lisa (My University, 2022)
Interventions aimed at increasing women’s numeric representation in politics tend to solve the problem by tackling a lack of demand among gatekeepers. However, even where there is an increase in demand, it is still important to consider what is happening on the supply-side; that is, the circumstances under which individuals will put themselves forward to run for office. One factor that has been identified as an important predictor of whether someone will choose to do so is whether they receive encouragement to run. This paper explores whether such encouragement is gendered. We investigate this question using a unique data set of candidates who ran in the 2019 Irish local elections. We find that female candidates received more encouragement to run than their male counterparts and that they were also more likely to receive such encouragement from particular sources (elected politicians, spouses, family members).
PUBLISHED
Keywords: Local elections; Irish elections; Party politics; Gender and politics; Women’s representation; Inclusive Society; GENDER; Gender and Politics; Gender role attitudes & behaviour; Irish Politics; Political Behavior; Political Participation; Political Parties; Political parties; Politics and Gender; Gender